3x2 = -9 (divide both sides by 3) x2 = -3 (x would have to be the square root of -3)
x = ±√-3
x = ±√3i
Since you want to solve by factoring:
x2 = -3 add 3 to both sides
x2 + 3 = 0
x2 - 3i2 = 0
x2 - (√3i)2 = 0 Factor:
(x - √3i)(x + √3i) = 0
x - √3i = 0 or x + √3i = 0
x = √3i or x = -√3i
3x2-9x = 0 x(3x-9) = 0 x = 0 or x = 3
One factor is 3.
1 and 3
y2+7y=18 y2+7y-18=0 (y+9)(y-2)=0 y=-9 & y=2
2x2-12x-54 = 0 Solve by factoring or using the quadratic equation formula or by completing the square: (2x+6)(x-9) = 0 Therefore: x = -3 or x = 9
3x2-9x = 0 x(3x-9) = 0 x = 0 or x = 3
The coefficient is -3.
Solve by factoring.2x2 - 3x + 1 = 0
3x2 + 2x + 2 = 0 Can not be factored. You can however solve it for x: 3x2 + 2x = -2 x2 + 2x/3 = -2/3 x2 + 2x/3 + 1/9 = -2/3 + 1/9 (x + 1/9)2 = -5/9 x + 1/9 = ±√(-5/9) x = -1/9 ± i√(5/9) x = -1/9 ± i√5 / 3 x = -1/9 ± 3i√5 / 9 x = (-1 ± 3i√5) / 9
One factor is 3.
1 and 3
y2+7y=18 y2+7y-18=0 (y+9)(y-2)=0 y=-9 & y=2
1 x 157, 157 x 1
0
2x2-12x-54 = 0 Solve by factoring or using the quadratic equation formula or by completing the square: (2x+6)(x-9) = 0 Therefore: x = -3 or x = 9
9 x 27 equals 243
A + 9 = 21 A = 21 - 9 A = 12